The genesis of the GATT - Irwin, Douglas A. 1962-; Mavroidis, Petros C. 1959-; Sykes, A. O. 1954- (Cambridge University Press, 2008)
This book is part of a wider project on the economic logic behind the General Agreement on Tariffs and Trade (GATT). This volume asks: What does the historical record indicate about the aims and objectives of the framers of the GATT? Where did the provisions of the GATT come from and how did they evolve through various international meetings and drafts? To what extent does the historical record provide support for one or more of the economic rationales for the GATT? This book examines the motivations and contributions of the two main framers of the GATT, the United States and the United Kingdom, as well as the smaller role of other countries. The framers desired a commercial agreement on trade practices as well as negotiated reductions in trade barriers. Both were sought as a way to expand international trade to promote world prosperity, restrict the use of discriminatory policies to reduce conflict over trade, and thereby establish economic foundations for maintaining world peace
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: General Agreement on Tariffs and Trade (Organization) / History; GATT 1947 -- 1947 Oktober 30; Geschichte; Geschichte 1945-1965; Recht; Foreign trade regulation / History; Tariff / Law and legislation / History; Vorgeschichte; Handelsabkommen; Außenhandel